A Qualitative Look into Gendered Entrepreneurship in Turkey - Duygu Seckin Halac; Tutku Seckin Celik (Istanbul Business Research (IBR), 2018)
People have started to question mainstream, supposedly gender-neutral, entrepreneurship definitions and perceptions with the confrontations of feminist perspective. Considering entrepreneurship as a gendered concept, in this study we handled gender as a lens in entrepreneurship. The purpose of this study is to portray gender specific characteristics and perceptions of entrepreneurship in Turkey. With this objective, we analyzed interviews with entrepreneurs in two Turkish entrepreneurship-focused business magazines and one popular business blog consisting of valuable startup and women entrepreneurs' stories and interviews. We performed qualitative analysis on the content of these interviews to understand the perspectives of female and male entrepreneurs, and the differences between them as to their statements. We analyzed the choice of words and interviewees' discourses. As to the findings, the most referred element of gendered entrepreneurship is family embeddedness based on stereotypical beliefs and norm systems. In addition, this finding shows how culturally embedded beliefs deeply effect women's expectations/projections, barriers and needs concerning entrepreneurship. In Turkey, there is only a handful of studies concerning women entrepreneurship from the perspective of gender as a lens. Therefore, in this article, gender specific perceptions of entrepreneurship in Turkey as a developing and a masculine country were revealed.
Keywords: M0; 650; Gendered entrepreneurship; Women; Qualitative research; Content analysis; Gender in Turkey